Alveolar preservation with fibrin-rich plasma: clinical effects and radiographic analysis. Case Series - Pérez Hernández , Jorge Alberto (2025)
Objectives: To evaluate the clinical effects and radiographically analyze the effectiveness of fibrin-rich plasma (FRP) in post-extraction bone preservation in a resource-limited community, considering its potential to mitigate complications and facilitate future rehabilitation. Materials and Methods: A case series was conducted in San Vicente Chicoloapan, State of Mexico, analyzing four patients treated with FRP after dental extractions. The protocol included centrifugation of blood at 1300 rpm for 8 minutes to obtain FRP, which was placed in the alveolus after extraction. Clinical and radiographic follow-up was performed using Handy Dentist software to assess healing, changes in bone height, and density. Results: In all four cases, complete gingival healing was achieved without complications. The case with the longest follow-up showed 97.8% bone preservation at seven months. Radiographically, progressive densification of the treated bone and reduction of inflammation were observed. No infections, dehiscences, or significant postoperative pain were recorded. Conclusions: PRF has proven to be an effective technique for alveolar preservation, highlighting its applicability in economically challenged communities due to its low cost and accessibility. The findings support its use as a viable alternative in clinical practice.